Lifelong learning and environmental education - Apel, Heino [Verfasser]; Ahlberg, Mauri [Verfasser]; Bachiorri, Antonella [Verfasser]; Clover, Darlene E. [Verfasser]; Jong, Frank P.M.C. de [Verfasser]; Hale, Monica [Verfasser]; Jerzak, Leszek [Verfasser]; Knoll, Joachim [Verfasser]; Leal Filho, Walter [Herausgeber]; Papen, Uta [Verfasser]; Schemmann, Michael [Verfasser]; Tahir, Farrukh [Verfasser]; et al. (Lang, Peter, 1997)
Inhalt: KNOLL: Environmental education and UNESCO : some achievements; LEAL FILHO: The environment : a unifying theme for lifelong learning and adult education; JERZAK: Lifelong learning and environmental education in Poland; TIMEAK: Lifelong learning and environmental education in Slovakia; HALE: Environmental learning, employment and professional training in Europe; BACHIORRI: Environmental adult education : experiences, problems and perspectives in the Italian context; TAHIR: Adult education and the environment in Pakistan; APEL: Environmental education for adults in the Federal Republic of Germany seen from the point of view of "lifelong learning"; WALS/JONG: Community-based environmental education, school, culture and lifelong learning; AHLBERG: Improvement of environmental education as a tool for high quality lifelong learning; CLOVER: Understanding human-earth relationships through storytelling and memory; PAPEN: Adult learning : a key for the 21th century; SCHEMMANN: Introducing the yearbook on adult education. (BIBB2)
Keywords: G 2.5.3 Anschlussfähigkeit von Bildungsgängen; G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; S 2.3 Berufsbildungspolitik; I 1.5 Internationale Organisationen & Institutionen; I 2.3.4 Asien; I 2.2.2 Osteuropa; I 2.2.1 Westeuropa; I 2.2 Europa; Erwachsenenbildung; Umweltbildung; Lebenslanges Lernen; Bildungspolitik; UNESCO; Pakistan; Polen; Slowakei; Italien; Europa